Pengetahuan dan Perilaku Masyarakat terhadap Pandemi Virus Covid-19 - Mukharomah, Chusnul Feby; Ahmad, Mursalin; Pratama, Rizky; Sari, Madinda Puspita; Putri, Anidya Thoha; Maulana, Rasyid Muttaqim; Wibowo, Yunus Aris (LaGeografia, 2021)
Coronavirus Disease 2019 (Covid-19) is a new type of disease that appears and has not been previously identified in humans. The virus that causes Covid-19 is called Sars-CoV-2. Indonesia is one of the countries that has experienced an increase in the number of Covid-19 cases since March 2020. Sragen Regency is one of the areas affected by Covid-19, especially Karangmalang District. This study aims to determine the level of knowledge and behavior of the people of Karangmalang District, Sragen Regency about Covid-19 and to know the relationship between the two. This research uses quantitative research methods using descriptive statistical analysis. This research was conducted in Karangmalang District, Sragen Regency. The data used by researchers are primary data in the form of data from questionnaires from respondents and secondary data from official government agencies. The results of the analysis show that the people of Karangmalang Subdistrict have a good level of knowledge and behavior towards Covid-19 and provide awareness to the community so that they always maintain their health to avoid the Covid-19 virus and contribute thoughts on overcoming Covid-19 in Karangmalang District, Regency Sragen.